RESPON PERTUMBUHAN DAN HASIL KENTANG VAR. CINGKARIANG DAN POPULASI GULMA TERHADAP ISOLAT RIZOBAKTERI INDIGEN - Irawati Chaniago; Muhsanati Muhsanati; Novita Hera; Siska Hanifa; Ronauli Fernandes Simanjuntak (Jurnal Agroteknologi, 2023)
Potato (Solanum tuberosum L.) has been classified as major source of carbohydrate along with rice, wheat, and corn. As for other crops, potatoâ€™s growth and yield are always subject to weed interference. An experiment has been conducted to study the effect of indigenous rhizobacteria to promote the growth and yield of potato var. Cingkariang and weed population at Nagari Pakan Sinayan, Agam District, the Province of West Sumatra. The experiment used a completely randomized design with seven treatments and three replications. The treatments was rhizobacteria indigenous to potato farm at Nagari Pakan Sinayan i.e SWL2.2, Ag2L2S3.3, Ag2L2S4.2, Ag3L3S3.1, Ag3L3S5.1, Ag4S5.2, and one group of without the isolate. Data were analysed with analysis of variance and mean separation following DNMRT at 5%. Results demonstrated that indigenous rhizobacteria promoted plant height, number of branches, and the weight of potato tubers. The rhizobacteria also resulted in changes in weed population. Ten weed species were found prior to the experiment as follows: Ageratum conyzoides L.,Â  Alternanthera philoxeroides (Mart.) Griseb., Andrographis paniculata (Burm.f) Nees, Bidens pilosa L., Cyperus rotundus L., Crassocephalum crepidioides (Benth.) S. Moore, Eleusine indica L., Echinochola colona (L.) Link, Galinsoga quadriradiata Ruiz & Pav., dan Paspalum commersonii Lamk. However, three new weed species emerged during the experiment. They are Amaranthus spinosus L., Portulaca oleracea L., and Paspalum conjugatum P.J.Bergius indicating changes in weed population.